Bursal Restoration After Intermediate And Intermediate Plus Infectious Bursal Disease Virus Vaccination - Castro, María; Saume, Elsy; García, Judith; Perozo, Francisco (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
Infectious bursal disease (IBD) is an acute, contagious, viral disease of young chickens characterized by diarrhea, vent picking, trembling, incoordination, inflammation followed by atrophy of the bursa of Fabricius and by variable degrees of immunosuppression. The diseases is caused by the infectious bursal disease virus (IBDV) which upon its antigenic characteristics and pathogenicity has been classified as classic (mild, intermediate and intermediate plus) strains, very virulent IBDV (vvIBDV) and variant strains. With the widespread presence of vvIBDV, the poultry industry has resorted to the use of less attenuated vaccines raising the concern about bursal integrity after vaccination. IBD vaccination using intermediate plus vaccine strains can temporarily deplete the bursal follicles and interrupt the normal B-cell development; if the damage is reversible this process can be followed by B-cell repopulation and histological regeneration. In order to assess this bursal restoration process, specific pathogen free birds were vaccinated with intermediate and intermediate plus IBDV vaccine and bursas were evaluated by histopathology and immunohistochemistry. Both B and T cells were detected in the recovering bursas. At the end of the trial, signs of bursal regeneration and B cell repopulation were observed in the intermediate IBDV vaccinated birds. The bursal restoration process was impaired or delayed in the intermediate plus vaccine group. Relevance of B and T cell repopulation is discussed